PERANCANGAN MODEL PENDUGAAN EFEKTIVITAS WADUK RESAPAN DI KOTA BOGOR TERHADAP OPTIMALISASI AKUIFER AIRTANAH - Sudaryo Broto; Hadi Susanto (Diponegoro University, 2008)
Flooding is a crucial problem in Jakarta city and there were many ideas to solve that problem, such ascanals development, land use management, applying soil conservation technique, check dam building,injection well, reservoir dam until rain moving technique. Reservoir dam is chosen by many experts as asolution to solve about flooding in order to increase and accelerate the rate of percolation to groundwaterinto their aquifer. this research is preliminary investigation to calculate the effectively of reservoir damthat is consider with water balance and groundwater flow into reservoir dam. In this research is developedby tank model that combine with 2 D of groundwater flow direction based on groundwater level